Reclaiming the cultural landscape of the Minangkabau in Negeri Sembilan - Haza Hanurhaza binti Md Jani (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2013)
This study fundamentally discusses the importance of reclaiming the Minangkabau cultural landscape in Negeri Sembilan. The notion of reclaiming the loss of culture is perceived as an important initiative towards protecting cultural landscape values. Therefore this study was conducted to provide understanding towards the importance of reclaiming cultural landscape in order to protect i) traditions, ii) local practices and iii) sense of identity. For that reason, it is important to identify the types of cultural landscapes that are significant to the tradition of the Minangkabau in Negeri Sembilan, to assess the existing condition of Minangkabau practices, as well as to assess the influence of cultural landscape towards the local identity of Minangkabau in Negeri Sembilan. This study employed a combination of quantitative and qualitative methods, namely questionnaire surveys and semi-structured interviews. The analyses were carried out by using the Statistical Package of Social Science (SPSS) version 20 and discourse analysis. The findings show a decline in the Minangkabau tradition, including the fact that the local practice is slowly diminishing and eventually causing the loss of a sense of identity. Due to these reasons, reclaiming the cultural landscape of the Minangkabau is seen as an initial step to rectify the current condition of the Minangkabau culture. It is also discovered that the perception towards the traditions, local practices and identity also contribute to further understanding the purpose of reclaiming the culture as a whole. Thus the findings demonstrates four aspects on the perceptions which are i) definition and representation of the Minangkabau ii) awareness on the local identity of the Minangkabau iii) the intervening factors of the declination of the Minangkabau and iv) ideal suggestions. This study has contributed to increase our knowledge on the level of understanding, responsibility and appreciating the Minangkabau traditions, local practices and identity.